Comparative analysis of power aware routing protocols in mobile ad-hoc network - ., Meenu; Vivek Jaglan, Dr; Agrawal, Akshat (International Journal of Engineering and Technology, 2018)
The Mobile Ad-Hoc network is a self-governing wireless network having dynamic topology and scattered mobile nodes. Limited power supply is the major challenge in wireless Ad-Hoc networks. Thus, for overall functioning of the ad-hoc network, efficient power conser-vation mechanism becomes the critical and most important component in ad-hoc network. Various power aware routing mechanism have been evolved to preserve energy, prolonging the life span of its nodes and thus of the network itself. Various other metrics for preserving energy also considered viz. selecting shortest path from source to destination, remaining battery power , fair distribution of traffic load among the nodes and minimizing the total transmission power with a view to increase the network life span and link stability. In this paper, various proposed protocols and recent energy conservation mechanisms are studied for mobile ad-hoc network. After analyzing the existing works it has been observed that there are still several areas where we can give more focus in the future.